Insulin Resistance Is Associated With Higher Intramyocellular Triglycerides in Type I but Not Type II Myocytes Concomitant With Higher Ceramide Content - Coen, Paul M.; Dubé, John J.; Amati, Francesca; Stefanovic-Racic, Maja; Ferrell, Robert E.; Toledo, Frederico G.S.; Goodpaster, Bret H. (Diabetes (New York, N.Y.), 2010)
Insulin Resistance Is Associated With Higher Intramyocellular Triglycerides in Type I but Not Type II Myocytes Concomitant With Higher Ceramide Content Paul M. Coen 1 , John J. Dubé 1 , Francesca Amati 2 , Maja Stefanovic-Racic 1 , Robert E. Ferrell 3 , Frederico G.S. Toledo 1 and Bret H. Goodpaster 1 1 Division of Endocrinology and Metabolism, Department of Medicine, University of Pittsburgh, Pittsburgh, Pennsylvania; 2 Department of Health and Physical Activity, School of Education, University of Pittsburgh, Pittsburgh, Pennsylvania; 3 Department of Human Genetics, Graduate School of Public Health, University of Pittsburgh, Pittsburgh, Pennsylvania. Corresponding author: Bret H. Goodpaster, bgoodatpitt.edu . Abstract OBJECTIVE We tested the primary hypotheses that sphingolipid and diacylglycerol (DAG) content is higher within insulin-resistant muscle and that the association between intramyocellular triglycerides (IMTG) and insulin resistance is muscle fiber type specific. RESEARCH DESIGN AND METHODS A nested case-control analysis was conducted in 22 obese (BMI >30 kg/m 2 ) women who were classified as insulin-resistant (IR; n = 12) or insulin-sensitive (IS; n = 10), determined by hyperinsulinemic-euglycemic clamp (>30% greater in IS compared with IR, P < 0.01). Sphingolipid and DAG content was determined by high-performance liquid chromatography–tandem mass spectrometry. Fiber type–specific IMTG content was histologically determined. Gene expression was determined by quantitative PCR. RESULTS Total (555 ± 53 vs. 293 ± 54 pmol/mg protein, P = 0.004), saturated (361 ± 29 vs. 179 ± 34 pmol/mg protein, P = 0.001), and unsaturated (198 ± 29 vs. 114 ± 21 pmol/mg protein, P = 0.034) ceramides were higher in IR compared with IS. DAG concentrations, however, were similar. IMTG content within type I myocytes, but not type II myocytes, was higher in IR compared with IS subjects ( P = 0.005). Insulin sensitivity was negatively correlated with IMTG within type I myocytes ( R = −0.51, P = 0.026), but not with IMTG within type II myocytes. The proportion of type I myocytes was lower (41 vs. 59%, P < 0.01) in IR subjects. Several genes involved in lipid droplet and fatty acid metabolism were differentially expressed in IR compared with IS subjects. CONCLUSIONS Human skeletal muscle insulin resistance is related to greater IMTG content in type I but not type II myocytes, to greater ceramide content, and to alterations in gene expression associated with lipid metabolism. Footnotes The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Received July 6, 2009. Accepted October 4, 2009. © 2010 American Diabetes Association